Risk reporting environment in Malaysia and the influence of corporate governance mechanisms - Ag Kaifah Riyard Kiflee; Mohd Noor Azli Ali Khan; Mathew Kevin Bosi (Human Resource Management Academic Research Society (HRMARS), 2020)
The aim of this study is to investigate the nature of risk information within Malaysia annual report and also to investigate potential determinants who influence the risk disclosure practice. Past accounting scandals and also the failure of financial system in 2007/2008 has triggered the need for sound corporate governance and also comprehensive risk management plan. A total of 167 companies based on a random sample were chosen from Bursa Malaysia from 2008 till 2017. This study also employed content analysis to measure the level of risk information. Based on the result, it is found that for the last 10 years, companies in Malaysia has increase their disclosure practice which this can be refer from the positive upward trend graph. This study found that all the selected corporate governance is positively and significantly influenced the risk disclosure practice among listed companies in Malaysia.